An Assessment of the Strategy of Working Capital Management in Polish Energy Companies - Zimon, Grzegorz (International Journal of Energy Economics and Policy, 2019)
Working capital is a kind of a buffer that protects an enterprise against the loss of financial liquidity. Therefore, managing it is a key element from the point of view of financial security in every company. The purpose of the articles is to analyze working capital management in the largest Polish energy companies. In general, state-owned companies, especially those operating in the energy sector, have no problems with managing liquidity or working capital. However, recently in Poland, the turmoil associated with an increase in energy prices resulting largely from political licks have caused rapid drops in energy companies in the market. In such a situation, it is worth analyzing the working capital management strategies in detail. The analysis was carried out on the group of the largest Polish energy companies. Keywords: working capital, energy companies, strategy JEL Classifications: G10; G33; Q43 DOI: https://doi.org/10.32479/ijeep.8406